ISOLASI DAN IDENTIFIKASI SENYAWA PENANGKAP RADIKAL 2,2-DIFENIL-1-PIKRIHIDRAZIL DARI KULIT BATANG BIDARA (Zizyphus mauritiana Auct. non Lamk.) - , PUTU OKA SAMIRANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The presence of excessive free radicals often leads to many degenerative diseases. This study aimed to isolate and identify the antioxidant compounds from the stem bark of Jujube tree (Zizyphus mauritiana Auct. non Lamk.). Isolation was conducted by bioassay guided fractionation, while antioxidant activity was assayed by DPPH radical scavenging method. The methanol extract of the stem bark was triturated into fraction n-hexane, ethyl acetate and methanol extract residue and all of them were examined for their DPPH radical scavenging antioxidant activity. The ethyl acetate fraction were then separated by repeated vacuum liquid chromatography (VLC) and purified using preparative TLC to obtain the active isolate. The purity of the isolate was evaluated by TLC method and melting point measurement. The structure of the isolate was identified chemically using various spray reagent and UV-Vis, IR, LC-MS and 1H-NMR spectroscopic method. The methanol extract, n-hexane fractions, ethyl acetate fraction, methanol extract residue and fractions derived from the separation of ethyl acetate fraction were determined for their total phenolic and flavonoid content. The results showed that the methanol extract residue containing the highest total phenolic (36.29 % w/w EGA), while E4 fraction containing the highest total flavonoids (21.31% w/w EQ). The active isolate having the DPPH radical scavenging activity with IC50 of 7.58 ï/mL. Based on spectroscopic analysis, active isolate contains triterpene compound which condense with p-coumaroyl group and their have trans configuration.